1990
DOI: 10.1109/29.103070
|View full text |Cite
|
Sign up to set email alerts
|

Generalized target description and wavelet decomposition (sonar)

Abstract: Generalized target description by means of colored bright spots (Altes [Z]) is very attractive for recognition or classification tasks in active sonar applications. In this correspondence, we show how such a description can be achieved directly from the impulse response to identify. It turns out that the resulting procedure is in close connection with the recently introduced technique of wavelet decomposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The wavelet needed however, is the autocorrelation of the Altes signal u(t). Moreover, it is shown that such a wavelet is admissible [6] and its shape partially resembles the Grossman Monet wavelet [6] for specific choices of the constants n,g, and c. The multiscale representations of the impulse response by wavelet decomposition correspond to different levels of integration and differentiation and hence different geometrical substructures of the target. It is shown in [81 that by using the autocorrelation of u(t) as a wavelet, then the scale parameter (a) is defined as a=g.…”
Section: Target Signature Description Using Waveletsmentioning
confidence: 98%
See 4 more Smart Citations
“…The wavelet needed however, is the autocorrelation of the Altes signal u(t). Moreover, it is shown that such a wavelet is admissible [6] and its shape partially resembles the Grossman Monet wavelet [6] for specific choices of the constants n,g, and c. The multiscale representations of the impulse response by wavelet decomposition correspond to different levels of integration and differentiation and hence different geometrical substructures of the target. It is shown in [81 that by using the autocorrelation of u(t) as a wavelet, then the scale parameter (a) is defined as a=g.…”
Section: Target Signature Description Using Waveletsmentioning
confidence: 98%
“…Flandrin et al [6], noted that the matched filter based system proposed by Altes [29] is equivalent to evaluating the wavelet transform of the target impulse response. The wavelet needed however, is the autocorrelation of the Altes signal u(t).…”
Section: Target Signature Description Using Waveletsmentioning
confidence: 99%
See 3 more Smart Citations